Longevidade das resinas compostas em dentes posteriores - DIAS, Denis Franco (2018)
The biggest improvement in researches for the development of the composite resin have offered the dental surgeons the possibility of using them as the best option for restauration of anterior and posterior teeth. However, this novelty brought doubts about its durability and which factors could intermeddle in a successful restauration. Many studies show that these factors could be related: Properties of the material used in the procedure, the operator, and also factors related to the patient as well, such as: Oral hygiene, cariogenic diet and salivary abnormalities. Due to this, the restauration protocol consider all the enumerated factors above mentioned to achieve the best possible outcome in the restoration’s durability. This article is focused on show an analysis of the literature, considering the longevity of composite resin’s restorations and the main causes of failure.